Antimicrobial Susceptibility Profiling and detection of Cefotaxime- Resistant Escherichia coli from Commercial Laying Hens, Indigenous Ducks and Chickens in Ibadan, Nigeria (2024)
Cefotaxime is a critically important antimicrobial agent for thè treatment of infections in humans and animals. The upsurge in thè incidence of cefotaxime-resistant Escherichia coti from animai sources is of global public health importance. Avian pathogenic Escherichia coti is a Gram negative zoonotic bacterial pathogen. Infections by Escherichia coti usually occur following consumption of foods and water contaminated with faeces. The development of antimicrobial resistance in Escherichia coti is a concem worldwide. This study evaluated thè prevalence, antimicrobial susceptibility and cefotaxime resistant Escherichia coti in commercial laying hens, indigenous ducks and chickens in Ibadan, Nigeria. Cefotaxime resistant Escherichia coti isolates from thè cloacae of these poultry sources were tested for antimicrobial agents. The overall isolation rate of cefotaxime resistant Escherichia coti was 6.5% (6/93), 3.2% (3/93) and 10.0% (20/200) from indigenous ducks, indigenous chickens and commercial laying hens respectively. Cefotaxime resistant Escherichia coti isolates were 89.7%, 86.2%, 65.5%, 55.2%, 37.9%, 27.6%, 20.7% and 20.7% resistant to sulphamethoxazole, tetracycline, ceftazidime, amoxicillin -clavulanic acid, chloramphenicol, ciprofloxacin, gentamicin and ceftriaxone respectively. Whereas, 75.9%, 68.9%, 62.1%, 51.7%, 41.4%, 27.6%,10.3% and 10.3% susceptible to ceftriaxone, ciprofloxacin, gentamicin, chloramphenicol, amoxicillin-clavulanic acid, ceftazidime, sulphamethoxazone and tetracycline respectively. Multidrug resistant (MDR) was observed in 89.7% (26/29) of thè isolates which exhibited 2 (in indigenous ducks), 3 (in indigenous chickens) and 13 (in commercial laying hens) different MDR pattems to 7 antimicrobial classes of drug. Higher isolation rate of cefotaxime resistant Escherichia coti and remarkable numbers of thè isolates from commercial laying hens showed multidrug resistant than that of indigenous ducks and chickens. Misused of drugs was predicted in commercial laying hens. This study showed that thè indigenous ducks and chickens harbour multidrug resistant Escherichia coti and may contribute to environmental contamination through faecal shedding.